REFORMS AND CHANGES AT THE NEW STAGE OF SOCIETY'S DEVELOPMENT ARE A FACTOR OF NATIONAL GROWTH AND DEVELOPMENT (American Journal of Research in Humanities and Social Sciences, 2022)
Today, the results of the reforms carried out in the historical period - the years of independence - are fully manifested, our people set noble and great goals, live peacefully, and above all, their own strength and we are living in a time when we are achieving great results in building a democratic state and civil society. During the years of independence, high growth rates were achieved, economic, social and political stability was ensured in our society, its spiritual and educational foundations were strengthened, renewal and changes in all spheres of life, modernization of the country bold steps towards it are recognized by the world community and prestigious international organizations.